Murder by Design - Bloch, Jon P. (St. Martin's Minotaur, 2004)
Opting to have his home remodeled on a popular cable reality show, celebrity gossip columnist Rick Domino is horrified when the consulting designer is found brutally murdered, a case for which Rick teams up with unstylish but attractive police detective Terry Zane.
Keywords: Crimes against; Fiction; Fiction; Hollywood (Los Angeles; Calif.); Fiction; Interior decorators; Fiction; Television programs; Gossip columnists; dept.soc; faculty_collection